Malware and Windows APIs: A Dangerous Duo - Muhammad Taseer Suleman (International Journal for Electronic Crime Investigation, 2023)
This paper introduces its interaction with malware and Windows APIs (application programminginterface). The first section describes malware and investigates various types such as viruses, wormsand trojans, as well as provides a brief history of malware and its evolution. The second sectionprovides an overview of the Windows APIs. It shows how these interfaces allow software andoperating systems to communicate with each other. It also highlights the most commonly usedWindows APIs and their functions۔ The follow-up section explores how malware uses WindowsAPIs for malicious purposes، Explains the common methods used by malware to communicate withthese interfaces۔ Includes real-world examples of malware attacks that use some Windows APIs. Thestudy then turns its attention to the Windows API security mechanism, given the security measurestaken by Windows to prevent the use of unauthorized APIs۔ The importance of user account control(UAC) and various monitoring and access control systems has been highlighted. The next sectionintroduces the API Hoking and its application to malware. Which explains the strategies used bymalware to hook Windows APIs۔ The effects of API hooking and possible detection methods are alsodiscussed. This article provides an in-depth overview of real-world malware that exploits WindowsAPIs through case studies and analysis. Notable malware analyzes examples using family andAPI-based attacks۔ The article discusses security tools and ways to identify and block API-basedmalware, as well as how to design secure programs with Windows APIs Suggestions for this havealso been discussed. Finally, malware tactics targeting Windows APIs discuss potential trends andissues, as well as expected API security challenges in the Windows context. This study continues tolook at advances in Windows API security and their implications for malware prevention.